The Character in Transit: Rethinking Moral Education through Children’s Urban Experiences - Audrey Rosdiana Putri; Hisny Fajrussalam; Sofyan Iskandar; Wina Mustikaati; Primanita Sholihah Rosmana; Ihsan Abdul Patah (Indonesian Values and Character Education Journal, 2025)
The degradation of children’s character, such as declining discipline and responsibility, has become a major concern in primary education. Formal classroom learning is often considered ineffective in deeply internalizing moral values. This study aims to explore how elementary school students’ experiences in using mikrotrans public transportation contribute to character development. Employing a qualitative case study approach, the research involved seven participants, consisting of a school principal, a teacher, two parents, two mikrotrans drivers, and an education observer. Data were collected through observation, in-depth interviews, documentation, and focus group discussions (FGDs), and analyzed using the Miles and Huberman model. The findings reveal that experiences gained from using mikrotrans strengthen students’ character traits such as discipline, responsibility, independence, social awareness, tolerance, and communication. These findings highlight the urgency of expanding character education beyond classroom settings by integrating students’ daily mobility experiences as meaningful and contextual learning spaces. This research implies the need to develop strategies for character education that are grounded in real-life experiences and relevant to students’ everyday lives, particularly through the use of public transportation by elementary school students.